Efficient transcription of the glycolytic gene ADH1 and three translational component genes requires the GCR1 product, which can act through TUF/GRF/RAP binding sites. - Santangelo, G M (1990)
Glycolytic gene expression in Saccharomyces cerevisiae is thought to be activated by the GCR and TUF proteins. We tested the hypothesis that GCR function is mediated by TUF/GRF/RAP binding sites (UASRPG elements). We found that UASRPG-dependent activation of a heterologous gene and transcription of ADH1, TEF1, TEF2, and RP59 were sensitive to GCR1 disruption. GCR is not required for TUF/GRF/RAP expression or in vitro DNA-binding activity.